A study of the professional community of teachers in equity of teaching quality - Juliasandi, Mousafi; Rohman, Arif (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2019)
The high level of educational participation has not guaranteed the quality of education in a country. Especially developing countries, the issue of educational participation can be overcome with the maximum, but the problem that is still the agenda in various countries is about the equalization of the quality of education. This article is an article compiled based on literature review of the issues. One of the key factors causing inequality in the quality of education is the irregularity of the quality of educators which ultimately affects the inequality of teaching quality. The literature study conducted finding the teacher community is an effective solution to solve the problem. The professional community is an association of teachers to interact with each other and communicate in an integrated learning and teaching improvement. The professional community of teachers is considered to be able to overcome the quality of educators who are located in remote areas. The activities of this professional community of teachers can also be maximized by the use of various media such as internet network. Addressing the gap in teaching quality between remote and airspace will ultimately be able to address the inequalities of appropriate educational quality.